ARTEFAK PRASEJARAH DI KALIMANTAN SELATAN: KAJIAN PERSEBARAN DAN PERMASALAHANNYA - Sugiyanto, Bambang (Balai Arkeologi Kalimantan Selatan, 2007)
Prehistory artefact collection in Lambung Mangkurat Museum can to use as data to study of prehistory culture distribution and development in South Kalimantan province. Data about place identification or sites where the artefact founded can be use base of to ascertain moreover research step. In spite of, not all that identification place to represent place where artefact founded, so that need to ask where found the artefact mentioned. Space, time, and form aspect very important inspection and analysis prehistory artefact. This case inside, prehistory artefact collection of Lambung Mangkurat Museum only have of form aspect.